(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2023)
Poecilia reticulata (P. reticulata) is a species of tropical fish in the family Poeciliidae that is found all over the world and is a favorite in freshwater aquariums. The Malay name for this fish is "Ikan Gapi," although the English term "Guppy" has become more common. The Million Fish, or Rainbow Fish, as it’s known in other parts of the world. The goals of this research were to char-acterize the acetylcholinesterase that will be partially purified from P. reticulata brain extract using ammonium sulphate fractionation The screening results show that at 1 mg/L insecticide, acephate, dimethoate, trichlorfon and bendiocarb leads to 100% inhibition, whilst parathion, methomyl and malathion cause >90% inhibition. The AChE from P. reticulata is less sensitive to other species as far as the insecticides carbofuran, carbaryl, methomyl, bendiocarb, parathion, diazinon, chlorpyrifos with the exception of malathion, where the sensitivity of malathion to the AChE from was within the range of the AChE from other species such a E. electricus , Pangasius sp., Chan-na micropeltes, Clarias batrachus, H. nemurus, Tor tambroides, and Osteochilus hasselti.